Structure–activity relationship of immunomodulating pectins from elderberries. (10th July 2015) - Ho, Giang Thanh Thi; Ahmed, Abeeda; Zou, Yuan-Feng; Aslaksen, Torun; Wangensteen, Helle; Barsett, Hilde
Highlights: Immunomodulating polysaccharides were isolated from the berries of Sambucus nigra. Structural characterizations of pectins from elderberries are reported. Reduction of arabinose and side chains complexity influenced the bioactivities. Ramified regions are important for macrophage stimulation and complement fixation. LPS seems to have minor impact on NO production observed in active fractions. Abstract: The berries of Sambucus nigra have traditionally been used and are still used to treat respiratory illnesses such as cold and flu in Europe, Asia and America. The aim of this paper was to elucidate the structures and the immunomodulating properties of the pectic polymers from elderberries. All the purified fractions obtained from 50% ethanol, 50 °C water and 100 °C water extracts showed potent dose-dependent complement fixating activity and macrophage stimulating activity. The isolated fractions consisted of long homogalacturonan regions, in addition to arabinogalactan-I and arabinogalactan-II probably linked to a rhamnogalacturonan backbone. Reduced bioactivity was observed after reduction of Ara f residues and 1→3, 6 Gal by weak acid hydrolysis. The rhamnogalacturonan region in SnBe50-I-S3-I and SnBe50-I-S3-II showed higher activity compared to the native polymer, SnBe50-S3, after enzymatic treatment with endo-α-d -(1→4)-polygalacturonase. These results indicated that elderberries contained immunomodulating polysaccharides, where the ramified regions express the activities observed.